The influence of leadership and work flexibility on employee performance - Pricilla, Lidya; Octaviani, Irma Sari (Journal of Economics and Business Letters, 2024)
This research aims to determine the magnitude of the influence of leadership and work flexibility on performance and employee performance at PT. First, Logistics Service, Tanjung Priok Branch. The research method used in this research uses quantitative methods. This research took a sample of 82 respondents. Data analysis uses multiple regression analysis. The research results show that leadership and work flexibility have a positive and significant effect, both partially and simultaneously, on employee performance.